Improving Critical Thinking Ability Through an Active Learning Approach in the Context of French Language Class in High School - Aan Anne; Sofyan Sauri; Dian Penisiani (Nexus Publishing NXP, 2024)
The aim of this research is to describe improving critical thinking skills through an active learning approach in the context of French classes in high schools. This type of research is qualitative with descriptive methods. The aim of this research is to determine the effectiveness of critical thinking skills through an active learning approach in the context of French classes in high schools. The specific objectives are: First, to analyze the impact of an active learning approach on students' critical thinking abilities in French classes. Second, identifying active learning strategies that are most effective in improving students' critical thinking abilities. Third, students' perception of active learning experiences in improving their critical thinking abilities.